A Comparison of Postoperative Pain Score and Tramadol Consumption between Local Anesthetic Agent with and without Dexamethasone under Ultrasound-guided Dual-TAP Block in Patients Undergoing One Day Inguinal Hernia Surgery: a Double-Blind, Randomized Contr - Uthaiwan, Kanokwan; Sukantarat, Numphung (Thai Journal of Anesthesiology, 2025)
Background: Transversus abdominis plane (TAP) and Ilioinguinal/Iliohypogastric (IL/IH) nerve blocks (dual-TAP block) under ultrasound-guided is a regional anesthesia technique that effective in reducing postoperative pain after open inguinal hernia repair. The study is aimed to compare postoperative pain score, total tramadol consumption, and complications after one day inguinal hernia surgery between dexamethasone plus local anesthetic agent and local anesthetic agent alone under ultrasound-guided dual-TAP Block. Methods: A prospective, double-blind, randomized controlled study of 32 patients undergoing elective one day inguinal hernia repair was randomized into two groups. Group 1 (n=16) received unilateral dual-TAP block with dexamethasone plus local anesthetic agent. Group 2 (n=16) received unilateral dual-TAP block with only local anesthetic agent. The study assessed the postoperative pain score after operation at 0, 2, 4, 6 and 24 h, total tramadol consumption at 24 h, and complications after operation at 0, 2, 4, 6, 24 h and 7 days. Results: There were statistically significant differences in the numerical rating scale (NRS) between group 1 and 2 after operation at 2 to 24 h. Mean total tramadol consumption in 24 h in group 1 was significantly lower than in group 2. However, there were no statistically significant differences in complications between the two groups. Conclusion: Local anesthetic agent with and without dexamethasone for ultrasound-guided unilateral dual-TAP block in patients undergoing one day inguinal hernia surgery is relatively safe and effective. Both techniques reduce postope- rative pain scores total tramadol consumption in 24 h.